VARIASI WAKTU SALAT: Studi Kasus Masjid-Masjid Di Kota Parepare Dalam Prespektif Hisab Kontemporer Dan Hukum Islam - Faiz, ABD. Karim Faiz; Wahidin, Wahidin (ELFALAKY: Jurnal Ilmu Falak, 2022)
Prayer times in the Parepare city, such as at the Great Mosque of Parepare, the Senggol Grand Mosque of Parepare, and mosques in all sub-districts of Parepare City still occur differences and time differences. This is based on the author's observation on 18 October 2021. The time of maghrib prayer based on the adhan varies. One mosque calls to prayer at 5:53 pm, while another calls to prayer at 6:00 pm, 5:59 pm, and the latest at 6:02 pm. This problem is the basis of research on prayer time variations in Parepare City with a Contemporary Hisab Review and Islamic Law Analysis. The objective of this research is first, to describe the way or method of determining prayer times in Parepare City Mosques. Second, to analyse the accuracy of prayer times in Parepare City Mosques in the review of Contemporary Hisab. Third, to analyse, describe and compare the difference of prayer times in Parepare City. The result of this research is that the method of determining the prayer time of Parepare City Mosques varies (Ministry of Religion Schedule, Sheikh Sa'aduddin Djambek's Timetable, Prayer Time Application, Hisab Muhammadiyah Version). The accuracy of the praying time of the mosques in Parepare City from the perspective of contemporary hisab has three categories; accurate, inaccurate and passing the time of ikhtiyat (less and more not passing 2 minutes), inaccurate and fatal (passing 2 minutes). The variation of prayer times in the Parepare city from the perspective of Islamic law is that the schedule of the five daily prayers (Dhuhr, Asr, Maghrib, Isha' and Fajr) at the Al-Azhar Islamic Centre mosque, Al-Muttaqin Mosque and Nurul Asiah Mosque (especially for the Fajr prayer) is invalid, because it has not yet entered the time for the obligation to pray.